Occupations and Inequality: Theoretical Perspectives and Mechanisms - Andreas Haupt; Christian Ebner (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2020)
People's occupations are strongly related to multiple dimensions of inequality, such as inequalities in wages, health, autonomy, or risk of temporary employment. The theories and mechanisms linking occupations to these inequalities are subject to debate. We review the recent evidence on the relationship between occupations and inequality and discuss the following four overarching theoretical perspectives: occupations and skills, occupations and tasks, occupations and institutions, and occupations and culture. We show that each perspective has strong implications for how scholars conceptualize occupations and which occupational characteristics are seen as relevant when explaining inequalities. Building on this, we review and critically examine the relevant theories related to and the mechanisms of the relationship between occupation and wage inequality, as an example. We conclude that there is sound empirical knowledge available on the relationships between occupations and inequality; however, some of the mechanisms are still unclear.
Keywords: 300; Theory of occupations; Skills; Tasks; Occupation-specific mechanisms; Wage inequality; Theorie von Berufen; Fähigkeiten; Tasks; Berufsspezifische Mechanismen; Soziologische Theorie; Lohnungleichheit